2013
DOI: 10.1245/s10434-013-3053-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cytoreductive Surgery (CRS) with Hyperthermic Intraperitoneal Chemotherapy (HIPEC) in Patients Older Than 70 Years; Survival Benefit at Considerable Morbidity and Mortality

Abstract: Background Cytoreductive surgery (CRS)/Hyperthermic Intraperitoneal Chemotherapy (HIPEC) is associated with prolonged survival in selected patients with peritoneal surface disease. Yet, for elderly patients (older than 70 years of age) CRS/HIPEC is controversial, due to associated morbidity. Methods A retrospective analysis of a prospective database of 950 procedures was performed. Type of malignancy, demographics, performance and resection status, hospitalization, morbidity, mortality, and survival were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 21 publications
5
39
1
Order By: Relevance
“…Votanopoulos et al support stringent patient selection (including some of the above metrics) and noted that using these metrics for patient selection was key for prolonged survival. 48 Similar conclusions were reached in a study by Macrì et al 46 Although some studies have shown patient age to be negligible in CRS-HIPEC patient selection, patients >60 years of age with tumor stage T3 or T4 have been associated with a higher risk of gastric cancer PC. 47 In other words, in the absence of other known factors that affect response to CRS-HIPEC, patient age should not be a contraindication to receiving CRS-HIPEC.…”
Section: Importance Of Patient Selectionsupporting
confidence: 69%
See 2 more Smart Citations
“…Votanopoulos et al support stringent patient selection (including some of the above metrics) and noted that using these metrics for patient selection was key for prolonged survival. 48 Similar conclusions were reached in a study by Macrì et al 46 Although some studies have shown patient age to be negligible in CRS-HIPEC patient selection, patients >60 years of age with tumor stage T3 or T4 have been associated with a higher risk of gastric cancer PC. 47 In other words, in the absence of other known factors that affect response to CRS-HIPEC, patient age should not be a contraindication to receiving CRS-HIPEC.…”
Section: Importance Of Patient Selectionsupporting
confidence: 69%
“…These include in vitro chemotherapy sensitivity 45 and patient age. 20,46,47 For example, a study by Votanopoulos et al, 48 examined CRS-HIPEC in the elderly (mean age was 73 years old) and concluded that age alone was not a contraindication for the procedure. Votanopoulos et al support stringent patient selection (including some of the above metrics) and noted that using these metrics for patient selection was key for prolonged survival.…”
Section: Importance Of Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger scale studies are still needed to establish specific risk factors of morbidity and mortality in CRS-HIPEC in GC patients. On the other hand, we believe it remains reasonable to carefully evaluate and select the patients with the common risk factors of CRS-HIPEC morbidity including advanced age, smoking, high disease burden (such as PC index) and poor completeness of cytoreduction (CC) (6,11,12) before more specific data regarding GC are available.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The 3-month interval, referred to above, was chosen because of its precedent in defining the success of interventions in other cancer settings. 5,19,20 The decision to seek information on the morbidities of coronary artery disease and bleeding diathesis was based on a high likelihood of lowering the thresholds of transfusion and bleeding, respectively. Finally, overall survival, as calculated from the time of vaginal bleeding to death, was also reported.…”
Section: Medical Record Reviewmentioning
confidence: 99%